Air Pollution With 2.5 Micron Particulate Matters and Testing the Decay of the Aerosol Concentration as a Function of Time to Compare the Efficiency of AHPCOÂ® and Bi-Polar Units in Reducing the Indoor Particle Counts - Ghosh, Nabarun; Sherali, Nelofar; Hiranuma, Naruki; Banerjee, Prabir; Sherali, Shabnum; Romero, Rebecca; Rogers, Jim; Bennert, Jeff; Vitale, Jay; Saadeh, Constantine; Revanna, Chandini (European Scientific Journal, ESJ, 2018)
One of the top environmental concerns of the world today is air pollution, which is affecting our health every day (Bickerstaff & Walker, 2001). Studies have shown that air pollution has a major effect in human health by increasing sickness and death (Dockery, & Pope III, 1994). A major form of air pollution is aerosol; scientists describe it as tiny, airborne solid and liquid particles that are released by Earth's surface both naturally and as a product of human activities (Simmon, & Voiland, 2010; NOAA Earth System Research Laboratory [NOAA], 2017). Our biggest problem with air pollution is the aerosols in the form of Particulate Matter (PM), also known as particulate pollution. The most dangerous particulate matters are those which are less than 10 micrometers, because when inhaled, they can reach deep down into our lungs and even into our bloodstreams (U.S Environmental Protection Agency [EPA], â€œParticulate Matter (PM) Basic,â€ 2017). The purpose of this study was to test a new kind of air purifier, and help the public make the right choice for their health. In this research several experiments were conducted using the Air Oasis filter-less air purifier with Advanced Hydrated Photo Catalytic Oxidation (AHPCO) and Bi-polar units inside the fiberglass chambers to estimate the decay of aerosol concentration as function of time. In higher concentration a prominent rate of decay was measured when using the Air Oasis units however, there has not been any significant change at the lower concentration.